Physiological and biochemical traits of yeasts from soils of various ecosystems of East Antarctica - E. Gribanova; V. Miamin (Ukrainian Antarctic Journal, 2021)
The diversity of psychrophilic / psychrotolerant microorganisms from Antarctica is a preferred subject of study by microbiologists, in turn, the communities of endolithic and hypolithic yeast cultures are practically not studied, and the literature on the biotechnological potential of such microorganisms should cover important biomolecules in addition to cold-adapted enzymes. In order to study the characteristics and biopotential of yeast cultures isolated from soil samples of East Antarctica, a number of physiological and biochemical tests were carried out. This article provides a list of the studied morphological characteristics, and also describes the results of the study of enzymatic activities and biochemical properties. In the course of research, it was revealed that Antarctic yeast isolates have a wide range of enzymatic activities when growing on agar media: most isolates were characterized by the presence of lipolytic, amylolytic, DNase, urease activities and the production of esters; a much smaller number of isolates were capable of manifesting proteolytic, cellulolytic and pectolytic activities, the release of organic acids and the formation of starch-like compounds. The study of tolerance to stress showed the presence of resistance of the studied cultures to the effects of ultraviolet radiation with a wavelength of 254 nm and low concentrations of copper sulfate in the environment. A qualitative assessment of the level of glycogen in yeast cells by staining with Lugol's solution showed that one culture is capable of accumulating glycogen in significant amounts. Additionally, the ability of yeast cells to accumulate lipids with increasing age of cultures was shown. The destruction of the surface of the mineral motor oil by the culture broth made it possible to identify yeast isolates with high destructive activity. This experience allows us to consider Antarctic yeast cultures as promising producers of biologically active compounds. The variety and spectrum of physiological activities of the investigated isolates allows us to consider them as promising producers of biological compounds for use in medicine and biotechnology.